SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-1035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High- and Low-Pressure Electric Supercharging of a HDD Engine: Steady State and Dynamic Air-Path Considerations

Abstract: This paper numerically investigates the performance implications of the use of an electric supercharger in a heavy-duty DD13 diesel engine. Two electric supercharger configurations are examined. The first is a high-pressure (HP) configuration where the supercharger is placed after the turbocharger compressor, while the second is a low-pressure (LP) one, where the supercharger is placed before the turbocharger compressor. At steady state, high engine speed operation, the airflows of the HP and LP implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Compared with other electrically assisted boosting systems, the ETA can achieve higher fuel efficiency than the electric supercharger [5]- [7] and electric turbocompounding [8]- [10]. The electric supercharger and the turbocharger work as a twostage system, with the EM and compressor connected in series.…”
Section: T Cmentioning
confidence: 99%
“…Compared with other electrically assisted boosting systems, the ETA can achieve higher fuel efficiency than the electric supercharger [5]- [7] and electric turbocompounding [8]- [10]. The electric supercharger and the turbocharger work as a twostage system, with the EM and compressor connected in series.…”
Section: T Cmentioning
confidence: 99%
“…Due to the lower material stress, sealing stress and packaging issues, however, most research institution and automobile manufacturers currently employ LP configurations. 20,21 The e-boosting device, according to its performance, can be categorised into the following two clusters: 1) transient machines; 2) transient and steady-state machines.…”
Section: E-boosting Technologymentioning
confidence: 99%
“…Due to the lower material stress, sealing stress and packaging issues, however, most research institution and automobile manufacturers currently employ LP configurations. 20,21…”
Section: V E-boosting Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…They found that applying an electric turbo charging system improved transient responses and fuel efficiency. Salehi et al [18] investigated the effects of high and low pressure eSs on a heavy duty diesel engine, for both steady state and transient operations, and found that LP eS was more efficient with respect to transient responses, although the high engine speed response was improved with an HP eS.…”
Section: Introductionmentioning
confidence: 99%